2008
DOI: 10.1590/s1413-73722008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Gestação e a constituição da maternidade

Abstract: RESUMO.Na gravidez ocorrem mudanças biológicas, somáticas, psicológicas e sociais que influenciam a dinâmica psíquica individual e as demais relações sociais da gestante, e maneira como ela vive estas mudanças repercute intensamente na constituição da maternidade e na relação mãe-bebê. Assim sendo, o objetivo deste estudo foi investigar os sentimentos das gestantes sobre a maternidade, com destaque para a relação entre o período gestacional e a constituição da maternidade. Participaram do estudo 39 gestantes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
136

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 15 publications
0
7
0
136
Order By: Relevance
“…These studies have demonstrated that maternal--fetal attachment increases with the gestational age, which, in turn, is related to the perception of fetal movements. Piccinini, Gomes, Nardi, and Lopes (2004) interviewed pregnant women who showed higher levels of satisfaction and self-fulfillment as the gestational age increased, in association with the growth of the fetus and belly. Authors such as Nishikawa and Sakakibara (2013) concluded that maternal-fetal attachment is directly related to the increase of gestational age and the perception of active fetal movements.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have demonstrated that maternal--fetal attachment increases with the gestational age, which, in turn, is related to the perception of fetal movements. Piccinini, Gomes, Nardi, and Lopes (2004) interviewed pregnant women who showed higher levels of satisfaction and self-fulfillment as the gestational age increased, in association with the growth of the fetus and belly. Authors such as Nishikawa and Sakakibara (2013) concluded that maternal-fetal attachment is directly related to the increase of gestational age and the perception of active fetal movements.…”
Section: Methodsmentioning
confidence: 99%
“…With the arrival of the child, the mother-to-be goes through a readjustment of her life conditions, with the transition in her social role: as well as being a daughter, the woman is now to be a mother 4,5 . In this phase of life the pregnant woman can go through emotional instability, fear and anxiety 2,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Essa fala da paciente ilustra o entendimento acerca do contato emocional entre mãe e filho já na gestação e de que o mesmo se daria a partir dos movimentos do feto e da atribuição de significados da mãe aos mesmos, constituindo as primeiras experiências da paciente com sua filha (Brazelton, 1988;Piccinini, Lopes, Gomes, & Nardi, 2008).…”
Section: Discussão Do Casounclassified